Science‐based Targets for Antibiotics in Receiving Waters from Pharmaceutical Manufacturing Operations. (29th April 2019) - Tell, Joan; Caldwell, Daniel J; Häner, Andreas; Hellstern, Jutta; Hoeger, Birgit; Journel, Romain; Mastrocco, Frank; Ryan, Jim J; Snape, Jason; Straub, Jürg Oliver; Vestel, Jessica
ABSTRACT: In 2016, the United Nations declared the need for urgent action to combat the global threat of antimicrobial resistance (AMR). In support of this effort, the pharmaceutical industry has committed to measures aimed at improving the stewardship of antibiotics both within and outside the clinic. Notably, a group of companies collaborated to specifically address concerns related to antibiotic residues being discharged from manufacturing sites. In addition to developing a framework of minimum environmental expectations for antibiotic manufacturers, science‐based receiving water targets were established for antibiotics discharged from manufacturing operations. This paper summarizes the holistic approach taken to derive these targets and includes previously unpublished, company‐generated, environmental toxicity data. Key Points: A recommended approach for assessing the risks from antibiotic manufacturing discharges is presented that considers both environmental endpoints and antimicrobial resistance. Also included are previously unpublished industry data on environmental toxicity of antibiotics.